UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM PROSES BELAJAR PENGAJAR (PBM) MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH SMP NEGERI 5 PERCUT SEI TUAN - Ellinawati Ellinawati; Dian Angraini (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This research was motivated by the teacher's lack of understanding of the Teaching and Learning Process (PBM) of Model Contextual Teaching and Learning (CTL), especially at SMP Negeri 5 Percut Sei Tuan. In research, the researcher tried to proposing the action proposals so that teachers use the CTL Model in teaching and learning activities. The problem in this PTS is how the effectiveness of increasing Teacher Pedagogic Competence towards Supervising Academic Supervision at SMP Negeri 5 Percut Sei Tuan, Deli Serdang Regency. The specific objectives of this PTS activity are to: a) Increase the understanding of the teachers in developing PBM; b) Improve the skills in developing PBM in teaching and learning activities. While the general purpose of this school action research activity is to determine the understanding and skills of teachers towards lesson plans in teaching and learning activities at. The conclusions obtained from this PTS activity are 1) The teaching and learning process (PBM) activity of CTL carried out by the Principal of SMP Negeri 5 Percut Sei Tuan. It has been carried out well and has contributed to the increase in the understanding and skills of teachers about the Teaching and Learning Process (PBM) of Medol Contextual Teaching and Learning (CTL) 2) The results of the analysis show that the increase in teacher understanding and skills regarding the Teaching and Learning Process (PBM) of Medol Contextual Teaching and Learning (CTL) in teaching and learning This has implications for improving the quality of education in SMP Negeri 5 Percut Sei Tuan.